2023
DOI: 10.3389/fnagi.2023.1071391
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the common pathogenesis of Alzheimer’s disease and type 2 diabetes mellitus via microarray data analysis

Abstract: BackgroundAlzheimer’s Disease (AD) and Type 2 Diabetes Mellitus (DM) have an increased incidence in modern society. Although more and more evidence has supported that DM is prone to AD, the interrelational mechanisms remain fully elucidated.PurposeThe primary purpose of this study is to explore the shared pathophysiological mechanisms of AD and DM.MethodsDownload the expression matrix of AD and DM from the Gene Expression Omnibus (GEO) database with sequence numbers GSE97760 and GSE95849, respectively. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“… Lee and Lee (2021) constructed a co-expression network to identify COPS4, PSMA6, GTF2B, GTF2F2, and SSB as dysregulated transcription common factors between AD and DM. Ye et al (2023) identified 10 shared hub genes between AD and T2D. Afzal et al (2023) uncovered the mutual genomics motifs between AD and T2D via non-negative matrix factorization, and screened of six shared genes.…”
Section: Identification Of Shared Candidate Biomarkers Between Ad And...mentioning
confidence: 99%
“… Lee and Lee (2021) constructed a co-expression network to identify COPS4, PSMA6, GTF2B, GTF2F2, and SSB as dysregulated transcription common factors between AD and DM. Ye et al (2023) identified 10 shared hub genes between AD and T2D. Afzal et al (2023) uncovered the mutual genomics motifs between AD and T2D via non-negative matrix factorization, and screened of six shared genes.…”
Section: Identification Of Shared Candidate Biomarkers Between Ad And...mentioning
confidence: 99%
“…Previous studies uncovered genes and signatures crosstalk linked these two diseases [45][46][47][48]. Herein, DEGs between AD and control included 381 downregulated genes and 357 upregulated genes in the dataset GSE122063 (▶ Fig.…”
Section: Cross-analysis Of the Molecular Links Between Type 2 Diabete...mentioning
confidence: 99%